Effect of Top G2 Liquid Organic Fertilizer and Frequency of Application on Growth and Yield of Hotong (Setaria italica L.) - Regina Sonya Tomasoa; Jacob R Patty; Jean I Nendissa (Agrologia, 2022)
This study aims to determine the effect of application and timing of Top G2 liquid organic fertilizer on the growth and yield of hotong plants. The research design was a Randomized Block Design with two factorials, namely the concentration of Top G2 liquid organic fertilizer and application time, and each treatment was repeated 3 times. The results showed that the application of liquid organic fertilizer TOP G2 had no significant effect on plant height and number of leaves at 8 WAP, as well as panicle weight g, panicle length cm, weight 1000 seeds g, fresh root weight g and plant dry weight g. While the real weight of the plant fresh and very significant on the dry weight of the roots. The time of administration of 8 WAP showed that plant height and panicle weight were significant and leaf number, panicle length was cm, seed weight was 1000 g, root fresh weight was g, plant fresh weight was g, and plant dry weight was very significant. Meanwhile, root dry weight was not significant. The interaction of 8 WAP was not significant on plant height, number of leaves, panicle weight g, panicle length cm, root fresh weight g, plant fresh weight g, root dry weight g, and plant dry weight g. While the interaction is very significant at the weight of 1000 seeds.